The Influence of the Credit Policy of Commercial Banks on the Modernization of the Russian Economy Structure - Helena, Ternovskaya; Alexander, Lavrishko (Journal of Reviews on Global Economics, 2018)
The model for the development of the Russian economy is based on the need for its structural adjustment. A big role in this process is played by commercial banks, whose credit policy is not yet aimed at actively supporting of investment processes in the economy. The purpose of the article is to study the directions and instruments of the influence of credit activity of commercial banks on the sectoral structure of the Russian economy. Based on analysis of the characteristics of Russian bank's credit policy measures were proposed to enhance its targeted focus on the modernization of Russia's economic structure through the development and support of special lending programs, including with regard to spatial development requirements. For this, a methodology has been developed to justify the choice of the region for their most effective implementation using the Gale-Shapley theorem. The set of proposed measures can contribute to strengthening the role of commercial banks in ensuring sustainable development of the national economy based on the impact on its structure.